Experience in international clinical research: the HIV Prevention Trials Network. (December 2011) - Sista, Nirupama Deshmane; Karim, Quarraisha Abdool; Hinson, Kathy; Donnell, Deborah; Eshleman, Susan H; Vermund, Sten H
The HIV Prevention Trials Network (HPTN) is supported by the NIH to conduct randomized clinical trials to assess the efficacy of HIV prevention strategies and technologies to reduce HIV transmission between adults. A special focus of attention is on the use of antiretroviral drugs to prevent HIV transmission, both by reducing infectiousness among HIV-uninfected persons taking combination antiretroviral therapy (cART) and also by reducing susceptibility among HIV-infected persons taking antiretrovirals for pre-exposure prophylaxis. Studies may be developmental in nature to assess novel ideas for interventions or for assessing trial feasibility. However, pivotal efficacy trials to test HIV-specific prevention strategies and technologies are the main HPTN priority. Examples include a major protocol investigating the impact of expanded testing and linkage to care on HIV surveillance indicators in the USA (HPTN 065). Another protocol is addressing similar issues while also investigating how combinations of prevention approaches are best deployed to make a community-level impact in southern Africa (HPTN 071). HPTN 068 is evaluating a novel conditional cash transfer structural intervention to increase school completion rates in young girls and thereby reduce their HIV risk. Studies outside the US address the epidemic in most at-risk populations and include an assessment of opiate agonist therapy to reduce risk of HIV seroconversion among injection drug users (HTPN 058), methods to increase HIV testing rates (HTPN 043), as well as methods for reducing high-risk behaviors, and increasing adherence to cART in HIV-infected individuals (HPTN 062 and HPTN 063, respectively). The recent HPTN 052 study demonstrated that a 96% reduction in HIV transmission could be achieved between serodiscordant sexual partners by providing the infected partners with cART at a CD4 + cell count (350–550/µl) above the level that would usually qualify them for therapy in low- and middle-income countries. The immediate relevance to public health policy showcased in these trials is a paradigm for the HPTN: design and conduct of clinical trials using available licensed tools that can be rapidly translated for implementation ('Prevention NOW!'').